(untitled) (Journal on Excellence in College Teaching, 2024)
One of the definitions of "catalyst" is "an agent that provokes or speeds significant change or action" (http://www.merriam-webster.com/dictionary/catalyst). In higher education, some instructors search for interventions that might provoke significant learning change or action in their own development, their courses, in the behavior of their students, and in higher education in general. Faculty who actively engage teaching and learning journals and conferences find opportunities to encounter evidence-based interventions that may be catalysts for learning and development.